The effect of lycopene on hepatotoxicity of aflatoxin B1 in rats - Karaca, Aysegul; Yilmaz, Seval; Kaya, Emre; Altun, Serdar (Taylor & Francis Ltd, 2021)
Oxidative damage caused by aflatoxin (AF) in rat liver tissue and the inhibition effect of lycopene against this injury was investigated. Groups were formed as; control group (not treated), lycopene group (5 mg/kg/day, gavage for 15 days), AFB1 group (0.5 mg/kg/day, gavage for 7 days) and AFB1 + lycopene group. Lycopene administered simultaneously with AFB1. It was observed significant increase in malondialdehyde level, decrease in glutathione level, antioxidant enzyme activities in liver tissue of AFB1 group when compared with control group. It was determined to significantly increase in plasma aspartate transaminase, alanine transaminase, lactate dehydrogenase activities in AFB1 group when compared with control group. It was determined significant decrease in malondialdehyde level, plasma aspartate transaminase, alanine transaminase, lactate dehydrogenase activities and increase in glutathione level, antioxidant enzyme activities in AFB1 + lycopene group when compared with AFB1 group. This study suggests that lycopene which has antioxidant properties can be prevented from AFB1 induced hepatotoxicity.
Keywords: Aflatoxin; antioxidant enzyme; glutathione; lycopene; malondialdehyde